The antioxidant status in Trichinella Spiralis-infected rats, improved by Selenium supplementation - Margarita Gabrashanska; Svetlozara Petkova; Svetla E Teodorova (Open Journal of Chemistry - Peertechz Publications, 2019)
Appearance of free radicals and membrane lipid peroxidation are one of the most typical unwelcome effects caused by trichinellosis (a parasite infection). Here the oxidative-antioxidant status of male Wistar rats uninfected and infected with Trichinella spiralis (Nematoda) was studied. The purpose of the study was to test substances, significantly diminishing unfavorable peroxidation effects. Selenium was chosen as a suitable defense factor. It was used in the form of the organic compound Sel-plex (Alltech). Blood biomarkers were studied in the experiment. The animals were allocated into four groups. The experiment covered 8 weeks post infection. The results showed that Sel-plex restores antioxidant defense system in Se-supplemented animals. The oxidative marker was malondialdehyde concentration. The antioxidant markers were superoxide dismutase and glutathione peroxidase activities, and concentrations of Se and vitamin E. A mathematical model was firstly proposed for the time course of host body weight. The model solutions were in good agreement with the experimental data. The relative rates of body weight gain were determined as growth kinetic parameters. The supplementation of the rats with dietary Se improved their antioxidant status, as follows: an increase by 10% in SOD activity, 6% in GPx activity, 13% in Vitamin E concentration, 17% in plasma Se concentration, and 19% in liver Se concentration respectively. A decrease by 18% in serum MDA concentration was recorded in the infected and supplemented animals. A reduction 63% in the muscle larvae after Sel-plex application was established. At week 8 the body weight gain in the supplemented rats (both uninfected and infected) was by 30% higher, compared to that in unsupplemented ones. Thus, a selenium diet could be essentially beneficial in the treatment of diseases correlated with considerable oxidative stress.